PENGARUH KONSENTRASI AMMONIUM SULFAT ((NH4)2SO4) SEBAGAI SUMBER NITROGEN TERHADAP PRODUKSI BIOETANOL BERBAHAN BAKU Glacilaria sp. - Widayanti, Ni Putu; Susanah Rita, Wiwik; Ciawi, Yenni (Jurnal Kimia (Journal of Chemistry), 2013)
The aims of this research are to determine the concentration of reducing sugar and starch in Glacilaria sp. and to investigate the influence of the concentration of ammonium sulfate as nitrogen source on the production of bioethanol using Glacilaria sp. as the carbon source. The concentrations of ammonium sulfate employed were 0,25%; 0,50%; 0,75%; and 1% (w/v). The methods employed in this research were the determination of water content, glucose and starch concentration using Nelson-Somogyi method, determinating the optimum duration of fermentation, pH measurement, and the determination of  ethanol concentration. The results showed that the concentrations of reducing sugar and starch in Glacilaria sp. are 17,14% and 15,42%. The concentration of (NH 4 ) 2 SO 4 , which produced the optimum concentration of ethanol (1,04% (v/v) on seventh day), was 1% (w/v). The fermentation media containing (NH 4 ) 2 SO 4 of 1%; 0,75%; 0,5%; and 0,25% (w/v) produced optimum concentrations of ethanol, which were 0,96% (v/v) on fifth day; 0,78% (v/v) on seventh day; 0,74% (v/v) on seventh days; and 0,73% (v/v) on seventh day, respectively. The optimum concentration of (NH 4 ) 2 SO 4 was 1% (w/v), which produced maximum concentration of  bioethanol from Glacilaria sp., of 0,96% (v/v).
Keywords: Glacilaria sp., fermentation, ammonium sulphate, and bioethanol